The Influence of Socialization and Service Quality on the Effectiveness of the E-Retribution Program at the Bukittinggi City Trade and Industry Service - Miftahul Khairat; Dasman Lanin (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
This research stems from the problem of the ineffectiveness of the shop e-retribution program in Pasar Bawah Kota Bukittinggi. This is proven by data on the percentage of realization of shop levies which still has not reached its target or potential, namely realization in 2023 of 69.14%, in 2022 of 77.14%, and in 2021 of only 28.36%. The aim of this research is to determine the influence of socialization and service quality on the effectiveness of the e-retribution program at the Bukittinggi City Trade and Industry Service. The research method is associative research with a quantitative approach. Determination of the sample using purposive random sampling technique. The population is 560 shop levy payers in the Pasar Bawah, while the research sample is 233 respondents determined using the Slovin formula with an error rate of 5%. The research results show (1) socialization has a positive and significant effect on the effectiveness of the e-retribution program with a sig of 0.000 and an Adjusted R Square value of 47.1% (2) service quality has a positive and significant effect on the effectiveness of the e-retribution program with a sig of 0.000 and a value of Adjusted R Square is 41.1% (3) socialization and service quality simultaneously have a positive and significant effect on the effectiveness of the e-retribution program with a sig of 0.000 and an Adjusted R Square value of 53.3%.